Attitudes Toward a Pre-authorized Concealed Opioid Taper: A Qualitative Analysis of Patient and Clinician Perspectives - Bedford, Theresa; Kisaalita, Nkaku; Haycock, Nathaniel R.; Mullins, C. Daniel; Wright, Thelma; Curatolo, Michele; Hamlin, Lynette; Colloca, Luana (Frontiers in Psychiatry, 2022)
Standard opioid tapers tend to be associated with increased patient anxiety and higher pain ratings. Pre-authorized concealed opioid reductions may minimize expectations such as fear of increased pain due to the reduction of opioids and, prolong analgesic benefits in experimental settings. We recently observed that patients and clinicians are open to concealed opioid tapering. However, little is known about the “why” behind their attitudes. Based on this lack of data, we analyzed qualitative responses to survey questions on patients’ and clinicians’ acceptance of a concealed opioid reduction for chronic pain. Seventy-four patients with a history of high dose opioid therapy and 49 clinicians completed a web-based questionnaire with open-ended questions examining responses to two hypothetical clinical trials comparing a concealed opioid reduction pre-authorized by patients versus standard tapering. We used content analysis based on qualitative descriptive methodology to analyze comments from the patients and clinicians. Five themes were identified: informed consent; anxiety; safety; support; and ignorance is bliss, or not. These themes highlight the overall positive attitudes towards concealed opioid tapers. Our findings reinforce the importance of patient-centered care and are expected to inform the design of clinical trials from both the patient and clinician perspective. This qualitative study presents patients’ and clinicians’ attitudes toward hypothetical scenarios for a trial of pre-authorized reduction of opioids. The findings indicate positive attitudes and the relevance of engaging patients with effective decision-making processes.